2014
DOI: 10.1371/journal.pone.0087739
|View full text |Cite
|
Sign up to set email alerts
|

Adults' Arithmetic Builds on Fast and Automatic Processing of Arabic Digits: Evidence from an Audiovisual Matching Paradigm

Abstract: Several studies have shown that performance on symbolic number tasks is related to individual differences in arithmetic. However, it is not clear which process is responsible for this association, i.e. fast, automatic processing of symbols per se or access to the underlying non-symbolic representation of the symbols. To dissociate between both options, adult participants performed an audiovisual matching paradigm. Auditory presented number words needed to be matched with either Arabic digits or dot patterns. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
2
20
2
Order By: Relevance
“…The findings of this study contradict those reported by Sasanguie and Reynvoet (), who found that performance on a dots‐number word matching task does not explain variance in arithmetic. It is necessary to note, however, that Sasanguie and Reynvoet () only include numerosities from within the subitizing range, whereas in this study both numerosities within and outside the subitizing range are presented.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The findings of this study contradict those reported by Sasanguie and Reynvoet (), who found that performance on a dots‐number word matching task does not explain variance in arithmetic. It is necessary to note, however, that Sasanguie and Reynvoet () only include numerosities from within the subitizing range, whereas in this study both numerosities within and outside the subitizing range are presented.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of this study contradict those reported by Sasanguie and Reynvoet (), who found that performance on a dots‐number word matching task does not explain variance in arithmetic. It is necessary to note, however, that Sasanguie and Reynvoet () only include numerosities from within the subitizing range, whereas in this study both numerosities within and outside the subitizing range are presented. In contrast to Sasanguie and Reynvoet (), our findings indicate that both symbol‐magnitude associations and symbol‐symbol associations support adults’ arithmetic abilities, whereas processing numbers per se does not.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations